2015
DOI: 10.1186/s40623-015-0205-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of solar activity on performance of the IRI-2012 model predictions from low to mid latitudes

Abstract: This study investigates the impacts of solar activity on the performance of the latest release of International Reference Ionosphere (IRI) model version 2012 (IRI-2012)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 52 publications
6
39
0
1
Order By: Relevance
“…In addition, the model performance in estimating diurnal VTEC variations was found to be better during low solar activity phases than during high solar activity phases. Abdu et al (1996), Kakinami et al (2012), Kumar et al (2015), andMcNamara (1985) attempted to describe the model's capacity to estimate the TEC in low-and mid-latitude regions. However, so far nobody has conducted a study to investigate patterns of VTEC variation over Ethiopian regions during the rising phase of solar cycle 24.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the model performance in estimating diurnal VTEC variations was found to be better during low solar activity phases than during high solar activity phases. Abdu et al (1996), Kakinami et al (2012), Kumar et al (2015), andMcNamara (1985) attempted to describe the model's capacity to estimate the TEC in low-and mid-latitude regions. However, so far nobody has conducted a study to investigate patterns of VTEC variation over Ethiopian regions during the rising phase of solar cycle 24.…”
Section: Introductionmentioning
confidence: 99%
“…The IRI model provides many parameters, including Total Electron Content (TEC) electron density, ion and electron temperature, ion composition for a given latitude, longitude, time date at altitudes ranging from 60 km to 2000 km. IRI based TEC data is derived by integrating the electron density profile from the lower boundary to the user specified upper boundary [Kumar et al 2015]. In this study, in order to compute IRI_2012 TEC values, a web interface from the IRI homepage (URL-3) was used.…”
Section: Model Calculations 211 Iri_2012mentioning
confidence: 99%
“…5 and 6, we determined the uncertainties in the conductivity and the EEF associated with the empirical model outputs in order to precisely determine the confidence limit in their magnitude. Although a large number of works deal with the comparisons between neutral atmosphere data and MSIS model prediction (Richards 2002;Liu et al 2005;Burke et al 2007;Park et al 2008;Jeon et al 2011), observed ionospheric data and IRI model predictions Batista et al 1996;de Souza et al 2003;Sethi et al 2004;Bertoni et al 2006;Lühr and Xiong 2010;Kenpankho et al 2011;Oyekola and Fagundes 2012;Yue et al 2013;Kumar et al 2014Kumar et al , 2015, and geomagnetic field data and IGRF predictions (Lowes 2000;Lowes and Olsen 2004), uncertainties (or potential errors) of these empirical models have not been published, even in Bilitza and Reinisch (2008), Picone et al (2002), and Finlay et al (2010).…”
Section: Analysis Of Linear Fittingmentioning
confidence: 99%